Environmental, Social, And Governance (Esg), Sustainable Growth Rate (Sgr) And Firm Value On Stock Returns Esg Sector Leaders Kehati And IDX80 - Ardila, Dayang Najwa; Safitri, Heni (Trunojoyo University of Madura, 2024)
This study aims to analyze the relationship between ESG factors, SGR, and firm value on stock performance in the ESG Leaders KEHATI and IDX80 sectors. The research method used is associative research method. Associative research is usually conducted to evaluate the influence or relationship between the independent variable and the dependent variable. The sample in this study was selected based on certain criteria. In this case, the study used a sample of 51 companies listed on the ESGSKEHATI Index major evaluation for the period June to November 2023, and IDX80 major evaluation for the period August 2023 to January 2024. Testing the ESG variable shows that this variable has a positive influence on stock returns. This is known from the t-count value of 3.303 which is greater than the T table value (2.012), as well as the significance value (Sig.) of 0.002 which is smaller than 0.05. Testing the SGR variable shows that this variable has a negative effect on stock returns. This can be seen from the t-count value of -2.969 which is greater than the T table value (2.012), and the significance value (Sig.) of 0.002 which is smaller than 0.05. Testing the PBV variable shows that this variable has no significant effect on stock returns. This can be seen from the t-count value of 1.654 which is smaller than the T table value (2.012), as well as the significance value (Sig.) of 0.105 which is greater than 0.05. By analyzing the relationship between ESG factors, SGR, and firm value on stock performance, this research will provide valuable insights for companies in the ESG Leaders KEHATI and IDX80 sectors in developing sustainable business strategies and increasing market value.